DEVELOPMENT OF WEB-BASED QR BARCODE MEDIA OF ANCIENT HUMAN MATERIAL PRESCRIPT PERIOD IN CLASS X STUDENTS OF SMA NEGERI 1 PEKANBARU: PENGEMBANGAN MEDIA BARCODE QR BERBASIS WEB MATERI MANUSIA PURBA MASA PRAAKSARA PADA SISWA KELAS X SMA NEGERI 1 PEKANBARU - Renaldi; Suroyo; Nurdiansyah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Development of Web-based QR barcode media based on ancient human material from the preliterate period using the ADDIE model. The first stage is an analysis based on the findings, history learning at SMA Negeri 1 Pekanbaru still uses methods that are not yet effective so that the teaching and learning process only becomes one way, where the teacher still dominates and is the center of learning activities. The second stage is design. At this stage the author designs a product, namely Web-based QR barcode media. Creating a successful website requires careful planning and a structured process. The Third Stage is development. At this stage the author develops a product, namely Web-based QR barcode media. Create a website design according to the initial plan, then create and upload website content, including text, images, video and audio. Make sure the content is well structured and easy to access. The fourth stage is implementation or application. After carrying out the development, validation and revision stages from experts and getting a proper assessment and very suitable for field testing, then this QR barcode learning media is used. The fifth stage is evaluation. At this stage, an analysis of the quality of WEB-based QR barcode learning media is carried out after carrying out validation tests from material experts, media experts, and student responses. Based on the calculation results, it can be concluded that the development of Web-based QR barcode learning media is "Feasible" based on the material expert assessment stage of 73.8%, media experts 86% in the "Very Feasible" category and assessment of small group student responses to the media with a percentage of 90.8% , with the "Very Appropriate" category, and the assessment of large group student responses to the media with a percentage of 93.3% in the "Very Appropriate" category.